2019
DOI: 10.1186/s13068-019-1623-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving hydrocarbon production by engineering cyanobacterial acyl-(acyl carrier protein) reductase

Abstract: BackgroundAcyl-(acyl carrier protein (ACP)) reductase (AAR) is a key enzyme for hydrocarbon biosynthesis in cyanobacteria, reducing fatty acyl-ACPs to aldehydes, which are then converted into hydrocarbons by aldehyde-deformylating oxygenase (ADO). Previously, we compared AARs from various cyanobacteria and found that hydrocarbon yield in Escherichia coli coexpressing AAR and ADO was highest for AAR from Synechococcus elongatus PCC 7942 (7942AAR), which has high substrate affinity for 18-carbon fatty acyl-ACP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…Interestingly, GFC elution profile of AAR does not correspond to a monomeric fraction, instead, a broadly distributed peak-like pattern has been observed indicative of the co-existence of multiple-sized states of the protein in solution (Fig. S2 ), which was also previously reported by Kudo et al group 17 . The presence of other protein contaminants was ruled out as only a single band was observed in SDS-PAGE corresponding to the monomeric molecular weight of the AAR protein (Figs.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, GFC elution profile of AAR does not correspond to a monomeric fraction, instead, a broadly distributed peak-like pattern has been observed indicative of the co-existence of multiple-sized states of the protein in solution (Fig. S2 ), which was also previously reported by Kudo et al group 17 . The presence of other protein contaminants was ruled out as only a single band was observed in SDS-PAGE corresponding to the monomeric molecular weight of the AAR protein (Figs.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, GFC elution profile of AAR does not correspond to a monomeric fraction, instead, a broadly distributed peak-like pattern has been observed indicative of the co-existence of multiple-sized states of the protein in solution (Fig. S1), which was also previously reported by Kudo et al group [18]. The presence of other protein contaminants was ruled out as only a single band was observed in SDS-PAGE corresponding to the monomeric molecular weight of the AAR protein ( Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Example for such strategies can be understood by the research of Kudo et al (2019), wherein they had shown that when non-conserved ADO was engineered conversion efficiency of this enzyme was increased for hydrocarbon production. This strategy can be utilized for the enhanced synthesis of biofuels using type I polyketide synthases that has low solubility and high catalytic functioning, through polyketide biosynthetic pathway [ 57 ]. Clostridium acetobutylicum was also engineered to increase the butanol-to-ethanol ratio.…”
Section: Metabolic Engineering For Biofuel Productionmentioning
confidence: 99%